Hesperia Supplements (JSTOR)
The Hesperia Supplement series presents book-length studies in the fields of Greek archaeology, art, language, and history. Originally designed to accommodate extended essays too long for inclusion in the journal Hesperia, the series was started in 1937. Since that date the Supplements have established a strong identity of their own, and are now recognized as one of the most prestigious publication venues in Greek studies. They range in format from single author monographs, through excavation reports, to major edited collections on topics of interest to researchers in classics, archaeology, art history, and Hellenic studies. Hesperia Supplements appear irregularly, but there are usually one to two published each year. Each Supplement is peer-reviewed, edited, and produced to the highest standards.
Keywords: Architecture & Architectural History